Preparation and characterization of cellulose nanofibers from banana pseudostem by acid hydrolysis: physico-chemical and thermal properties - Merais, Mohammad Sobri; Khairuddin, Nozieana; Salehudin, Mohd Harfiz; Mobin Siddique, Md. Bazlul; Lepun, Philip; Chuong, Wong Sie (MDPI, 2022)
Cellulose is a biopolymer that may be derived from a variety of agricultural wastes such as rice husks, wheat straw, banana, and so on. Cellulose fibril that is reduced in size, often known as nanocellulose (NC), is a bio-based polymer with nanometer-scale widths with a variety of unique properties. The use of NC as a reinforcing material for nanocomposites has become a popular research issue. This research paper focuses on the production of banana pseudostem cellulose nanofiber. Nano-sized fiber was obtained from banana pseudostem through several processes, namely, grinding, sieving, pre-treatment, bleaching, and acid hydrolysis. The product yield was found to be 40.5% and 21.8% for Musa acuminata and Musa balbisiana, respectively, by the weight of the raw fiber. The reduction in weight was due to the removal of hemicellulose and lignin during processing. Transmission electron microscopy (TEM) analysis showed that the average fiber size decreased from 180 µm to 80.3 ± 21.3 nm. Finally, FTIR analysis showed that the fibers experienced chemical changes after the treatment processes.